Consumer preference for cement brands used in concrete production: the Ghanaian perspective. Issue 1 (31st December 2022) - Bonney, Stanley Owuotey; Song, Jianxue; Jingwei, Zhang; Peng, Yi
Abstract: The cement industry is rising rapidly along with the building industry globally. This makes it possible for more competitions that provide customers with preference considerations. The study aimed to contribute to knowledge by exploring consumer preferences for cement brands and factors that influence their selection of cement used for concrete production in Ghana. The study employed a quantitative survey approach. The study comprised of private homeowners (70.7%) and construction/estate companies (29.3%) in four major cities in Ghana. Purposive and accidental non-probability sampling techniques were adopted. There were 741 respondents to the study survey. The study found that consumers' preference for a particular cement brand were significant for Ghacem (F = 0.81, P < 0.01), Diamond (F = 0.71, P < 0.01), Dangote (F = 0.70, P < 0.01), CEMAF (F = 0.69, P < 0.01), Dzata (F = 0.62, P < 0.01), SOL (F = 0.61, P < 0.01), Supacem (F = 0.57, P < 0.01) and Savannah Cement (F = 0.55, P < 0.01). The findings further showed that the majority of consumers are influenced by factors such as brand name, durability, easy to work with, well packaged, available in nearby shops, and external factors such as recommendations from professionals, and friends/family. Among the demographic factors, gender (F = 0.686, P < 0.01), age (F = 0.577, P < 0.01), the duration of cement usage (F = 0.358, P < 0.01), and educational background (F = 0.038, P < 0.01) were found to have a significant influence on consumers' preference of a cement brand. This indicates that brand preference exists among consumers due to demographics and influencing factors, implying that, manufacturers and marketers could introduce product differentiation using these variables.